Proceedings of ICI Milan 2013 - Francesca Di Rosa (Frontiers Research Topics, 2014)
This Research Topic covers all of the major lectures and symposia addresses delivered by invited speakers at the 2013 International Congress in Immunology (ICI) at Milan, Italy, August 22-27, 2013.